(untitled) (Iter, 2022)
This present essay is about the poetic experience o f Salvatore Quasimodo through the panoramic evolution of his works, in which is underlined a series of antinomies: transparency-shadow, word-occurencet ownership-separability, inner landscape- originary soil. In each one of these cases exists the firm conviction that poetry is an ethical and an esthetical matter a message of companionship and clarity ofmen ’s destiny.